FILOSOFI DAKWAH “BANYU MILI” SANG WALI DI BUMI WILWATIKTA - Harun Arrosyid (Jurnal Inovasi Penelitian, 2022)
The intention of the scientific paper formulation is to fine analyze (1) the design of Sheikh Jumadil Kubro’s da’wah in the spread of Islam in Majapahit (2) the implementation model of Sheikh Jumadil Kubro’s da’wah in the spread of Islam in Majapahit (3) the implecations of Sheikh Jumadil Kubro’s da’wah design of the development of Islam in Majapahit. A qualitative approach with the type of historical research is a research implementation format. The research hierarchy includes (1) theme selection (2) aggregation (search and collection of sources) (3) source criticism (4) synthesis (5) presentation of articles in analytical descriptive manner. The result of the research determined that (1) Sheikh Jumadil Kubro’s da’wah design with philosopy of “banyu mili” through tradition centered design, character centered design and dialogue centered design is a da’wah paradigm that has harmonization with the concept of “tutwuri hangiseni” and Islamic teaching principles (2) model the humanist-sufistic approach as a representation of the da’wah bil hikmah wal mau’izatul hasanah al mujadalah billati hiya ahsan provides an affirmation of Islamic da’wah in the Majapahit era (3) the formulation of the da’wah philosopy “banyu mili” has positive implications for the development of Islam in Majapahit as a powerful kingdom with a multi-faceted icon, cultural and multi-religious.